PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP BURNOUT PADA PERAWAT RSUD KARDINAH KOTA TEGAL - Bimba Ario Pradana; Rudi Suryo Kristanto; Dwi Suryanto Hidayat (Magister Manajemen STIE Bank BPD Jateng, 2017)
This study aims to examine and analyze whether there is influence of the working environment and workload against exhaustion in nurses. Observed object are ministerial government agencies that district general hospitals. The sample in this study is a hospital nurses Kardinah Tegal City with a number of 201 nurses as respondents, which consisted of 140 nurses inpatient and 61 outpatient nurse. The sampling technique in this study is purposive sampling and analysis method used is multiple linear regressions. Results of analysis showed the environment variabel inpatient nurses working in a negative influence on weariness.While working environment variabel on an outpatient nurse has no effect on tension. Variable capacity of nurses inpatient and outpatient positive effect on burnout. Of this study obtained a value of 0,525 or 52,5%. It means that 52,5% of burnout variables can be explained by the independent variables are the working environment and workload. The residual 47,5% is explained by other variable outside variable examined.